Investment strategies in the scope of takeovers : drivers of Mergers & Acquisitions success probability - Ghebregergis, Bana (2021)
Mergers and acquisitions (M&A) are a fundamental part of corporate finance activity and one of the most prevalent inorganic growth instruments in the corporate landscape. However, less than 50% of all announced transactions are closed, either because the parties involved do not find a satisfactory agreement, because the target successfully adopts defensive techniques, or because the target finds an alternative acquirer. Understanding why deals are abandoned permits us to assess the likelihood of a planned transaction better to succeed, reducing the costs of an announcement and allowing investors to profit from merger arbitrage. Therefore, the present work is dedicated to this fundamental topic and analyzes various microeconomic factors that influence the probability of M&A success. The study makes two contributions to the existing literature: First, a machine learning approach is used to determine whether an individual variable impacts M&A closing. Second, the relationship between the target’s capital structure and M&A success likelihood is observed. The results of this study provide empirical evidence that deal-specific variables, such as the nature of the bid and the payment method, have significant explanatory power explaining M&A success, while the targets leverage only shows moderate impact. The data set used in this study includes 8,649 M&A deals in the period from January 1990 to April 2019.